Analisis Kualitas Layanan E-Tracking J&T Cargo menggunakan COBIT 5 - Fenny Lestari; Tata Sutabri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In today's practical digital era, this has fueled the presence of companies operating in the field of technology-based logistics services, for example J&T Cargo. One of the industries currently developing in Indonesia is the logistics transportation services industry due to the growth of e-commerce over the last decade. J&T is a logistics company that helps customers pack and send their goods. J&T cargo e-tracking is a service used to track package information, track outlets and also check postage which can be done independently without having to go to the outlet, making it easier for consumers to obtain information quickly and more efficiently. This research focuses on the COBIT 5.0 domain Deliver, Service, and Support (DSS) framework which aims to obtain the level of satisfaction of users of the J&T Cargo E-Tracking service. So the research results show that the lowest current maturity level value in the DSS domain is the DSS02 process, namely at level 3 (Established Process) and the other 5, namely DSS01, DSS03, DSS04, DSS05, DSS06 are at level 4 (Predictable process). From the results of measuring the maturity level, the as-is and to-be values ​​are obtained which will be the targets for IT governance of E-tracking services at J&T Cargo.